Bottlenecks and Countermeasures for the Inclusion of Enterprise Data Assets in the Financial Statements in China - Zhang, Huan (Journal of Global Economy, Business and Finance, 2025)
In August 2023, China issued the “Interim Provisions on Accounting Treatment Related to Enterprise Data Resources”, which clarified the scope of recognition of data resources and accounting treatment standards, fundamentally promoting the process of data assetization in China and enabling the value of data assets to be presented and disclosed in financial statements. Judging from the theoretical development in the past two years and the practical operations of a few enterprises, the inclusion of enterprise data assets in the financial statements is still in the trial stage. Starting with clarifying the significance of data asset inclusion, this article further presents and analyzes the eight main bottlenecks of data asset inclusion, and then provides corresponding countermeasures one by one, hoping to give some help to the relevant enterprises.